Effect of multiphase radiation on coal combustion in a pulverized coal jet flame. (August 2017) - Wu, Bifen; Roy, Somesh P.; Zhao, Xinyu; Modest, Michael F.
Abstract: The accurate modeling of coal combustion requires detailed radiative heat transfer models for both gaseous combustion products and solid coal particles. A multiphase Monte Carlo ray tracing (MCRT) radiation solver is developed in this work to simulate a laboratory-scale pulverized coal flame. The MCRT solver considers radiative interactions between coal particles and three major combustion products (CO2, H2 O, and CO). A line-by-line spectral database for the gas phase and a size-dependent nongray correlation for the solid phase are employed to account for the nongray effects. The flame structure is significantly altered by considering nongray radiation and the lift-off height of the flame increases by approximately 35%, compared to the simulation without radiation. Radiation is also found to affect the evolution of coal particles considerably as it takes over as the dominant mode of heat transfer for medium-to-large coal particles downstream of the flame. To investigate the respective effects of spectral models for the gas and solid phases, a Planck-mean-based gray gas model and a size-independent gray particle model are applied in a frozen-field analysis of a steady-state snapshot of the flame. The gray gas approximation considerably underestimates the radiative source terms for both the gas phase and the solid phase. The gray coal approximation also leads to under-prediction of the particle emission and absorption. However, the level of under-prediction is not as significant as that resulting from the employment of the gray gas model. Finally, the effect of the spectral property of ash on radiation is also investigated and found to be insignificant for the present target flame. Highlights: A Monte Carlo–based nongray radiation solver is developed to study effects of radiation. Radiation alters the lift-off height, and the distribution of temperature andspecies for the target flame. Radiation alters the heat transfer mechanism of medium-to-large particles from convection-dominant toradiation-dominant. Accounting for the nongray effects of the gas phase is more important than accounting for those of the solid phase. The spectral properties of ash have insignificant influence on the test flame.